Characterization of anisotropically shaped silver nanoparticle arrays via spectroscopic ellipsometry supported by numerical optical modeling - Gkogkou, Dimitra; Shaykhutdinov, Timur; Oates, Thomas W. H.; Gernert, Ulrich; Schreiber, Benjamin; Facsko, Stefan; Hildebrandt, Peter; Weidinger, Inez M.; Esser, Norbert; Hinrichs, Karsten (Applied Surface Science, 2017)
The present investigation aims to study the optical response of anisotropic Ag nanoparticle arrays deposited on rippled silicon substrates by performing a qualitative comparison between experimental and theoretical results. Spectroscopic ellipsometry was used along with numerical calculations using finite-difference time-domain (FDTD) method and rigorous coupled wave analysis (RCWA) to reveal trends in the optical and geometrical properties of the nanoparticle array. Ellipsometric data show two resonances, in the orthogonal x and y directions, that originate from localized plasmon resonances as demonstrated by the calculated near-fields from FDTD calculations. The far-field calculations by RCWA point to decoupled resonances in x direction and possible coupling effects in y direction, corresponding to the short and long axis of the anisotropic nanoparticles, respectively.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Anisotropy; FDTD; Nanostructure characterization; Optical modeling; RCWA; Spectroscopic ellipsometry